2020
DOI: 10.3389/fpls.2020.546345
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Base of Mint Allelopathy: Menthone Affects Plant Microtubules

Abstract: Plants can use volatiles for remote suppression of competitors. Mints produce essential oils, which are known to affect the growth of other plants. We used a comparative approach to identify allelopathic compounds from different Mints (genus Mentha, but also including Cat Mint, Nepeta cataria, and Corean Mint, Agastache rugosa, belonging to sisters clades within the Mentheae) using the standard cress germination assay as readout. To understand the mechanism behind this allelopathic effect, we investigated the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 67 publications
1
35
1
1
Order By: Relevance
“…FTIR studies of ZnO and AZO nanoparticles show broad absorption bands at 1620 cm −1 and 3440 cm −1 were ascribed to O-H bending vibration modes of water molecules absorbed onto the ZnO and AZO nanoparticles [48]. A freshly collected mint leave contains water and a mixture of plant oils, such as mentone, menthol, and limonene [8]. Quantitative analysis in literature show that Mint species also contain phenolic compounds, flavonoids, and rosmarinic acid and its derivatives [50].…”
Section: Sensor Array Responsementioning
confidence: 99%
See 1 more Smart Citation
“…FTIR studies of ZnO and AZO nanoparticles show broad absorption bands at 1620 cm −1 and 3440 cm −1 were ascribed to O-H bending vibration modes of water molecules absorbed onto the ZnO and AZO nanoparticles [48]. A freshly collected mint leave contains water and a mixture of plant oils, such as mentone, menthol, and limonene [8]. Quantitative analysis in literature show that Mint species also contain phenolic compounds, flavonoids, and rosmarinic acid and its derivatives [50].…”
Section: Sensor Array Responsementioning
confidence: 99%
“…The effects are often species specific. For instance, a comparative analysis of germination inhibition in combination with activity-guided fractionation revealed that menthone/isomenthone released by Korean Mint (Agastache rugosa) caused a swift and complete breakdown of microtubules in the target plant such that germination (requiring microtubules for cell division and cell expansion) is blocked, while closely related compounds, such as menthol, were ineffective [8]. This specificity of biological action may be valorized for the development of novel, environmentally compatible bioherbicides that specifically affect a certain type of weed without damaging the useful crop [9].…”
Section: Introductionmentioning
confidence: 99%
“…A quantitative determination of the total amount of a particular VOC loaded into a MOF thin film can be carried out using a QCM. In the present case, the scent emitted from a plant consists of a large variety of different compounds, with their number typically exceeding 20 [36,37]. MOFs are highly porous with huge specific surfaces [35].…”
Section: Figurementioning
confidence: 99%
“…Botaniker des Karlsruher Instituts für Technologie (KIT) haben nun im Öl verschiedener Minzpflanzen nach weiteren, die Mikrotubuli hemmenden Verbindungen gesucht [2]. Dazu testeten sie zuerst, ob die Öle die Keimung – also das Wachstum – von Kressesamen beeinflussten und analysierten gleichzeitig mit Hilfe von Gaschromatografie die Zusammensetzung der Öle.…”
Section: Menthon Als Aktive Komponenteunclassified